Seismic Multiatributes Characterisation of Karst Distribution Pattern in an Isolated Middle Miocene Carbonate Platform: FX Field, Central Luconia Province Malaysia - Ab Rahman, S.S. (Slovnaft VURUP a.s, 2021)
Characterization of isolated carbonate build-ups in seismic is important as it is a well-known target for hydrocarbon explorations. Seismic attributes analysis is commonly used in seismic interpretation for reservoir characterization. This study aims to discuss and suggest more accurate attributes to characterize the external and internal anatomy of isolated carbonate build-ups. Central Luconia province is located in offshore Sarawak, Malaysia and is characterized by its widely spread subsurface isolated carbonate build-ups. Few previously published studies showed that the build-up's anatomy is unlikely similar from each platform due to the influence of sea-level fluctuation, tectonics, topography, and windward directions which play a huge role to influence the morphology. FX field which is located in the central region of the province has been selected for this study. Spectral decomposition, Chaos, and RMS amplitude were applied on FX field seismic cube to enhance the interpretation of karst architecture. The results show that spectral decomposition is one of the most recommended attributes to highlight the reef rim and karst architecture, chaos attribute highlighted the reef rim and RMS amplitude enhance talus distribution surrounding the platform. Dendritic patterns interpreted karst are well observed using spectral decomposition attributes and geometries were compared with the National Mulu Caves aerial photograph for a better understanding analogy comparison with a potential modern analogue. Â© 2021. All rights reserved.